Green Logistics Practices and Challenges in the Logistics Industry: Case study of SF Express - Huang Jiawei; Shi Ziyi; Song Yang (SHS Web of Conferences, 2024)
With the rapid development of China’s logistics industry, the integration of green logistics has become a key goal to achieve sustainable development. This study examines the current status of green logistics development in China, the challenges it faces, and its practice at SF Express, including the environmental impacts of traditional logistics processes, such as transportation emissions, excessive packaging, and the limited attention paid by companies to green logistics awareness. In addition, this study analyzes SF Express’ initiatives to optimize its logistics system, implement green transportation, reduce packaging waste, and promote low-carbon logistics through technological innovations such as drones and new energy vehicles. By adopting a green logistics framework that incorporates the “5Rs” principles, SF Express has made significant progress in reducing its environmental footprint. The study suggests that despite some successes, there are still challenges in promoting green logistics across the industry, such as the need for greater coordination with e-commerce partners and wider adoption of sustainable practices by employees at all levels of the organization.